(untitled) (Historia, 2021)
21 June 1987 marked the 100th anniversary of the founding in Holland of the Netherlands South African Railway Company with Dutch and German capital. It had the express aim of constructing a railway link between Pretoria and Delagoa Bay to make the South African Republic independent of the British South African harbours for her access to the outside world. However, when a temporary prohibition on the construction work on this line was imposed by the Transvaal government in 1888 because it had proved impossible to reach agreement with the concessionaire for the section of the line over Portuguese territory, the Company submitted a tender for the construction of a so-called steam tramway between Boksburg on the East Rand, where coal had been discovered, and Johannesburg. It was awarded the contract and the coal line of 27 km was opened on 17 March 1890, to become the first railway in the Republic. It was later extended to Springs in the east and Krugersdorp in the west. This pioneer railway in the Transvaal was significant in that it helped to overcome the fears and prejudices of the conservative Transvaal Afrikaners with regard to railway construction. It also played an important part in the economy of the early Witwatersrand by providing a regular supply of coal to the gold mines at reduced prices. The logistical problems in building such a railway in the interior, unconnected with any other railway, were considerable, and it says much for the company that it was able to surmount these difficulties. Op 21 Junie 1987 was dit presies 100 jaar sedert die stigting van die Nederlandsche Zuid-Afrikaansche Spoorweg-Maatschappij (NZASM), met Nederlandse en Duitse kapitaal, in Nederland met die oogmerk om vir die Zuid-Afrikaanse Republiek van president Paul Kruger ’n spoorwegverbinding met Delagoabaai in Mosambiek te bou wat die land onafhanklik van die Brits-Suid-Afrikaanse kolonies, die Kaapkolonie en Natal, sou maak wat sy verbinding met die buiteland betref. Die onderstaande artikel is bedoel as ’n herdenking van wat deur die maatskappy in die Republiek voltooi is.